PENGEMBANGAN MEDIA KOMIK DIGITAL BERBASIS APLIKASI CANVA PRO UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANTAR BUDAYA SISWA KELAS IV SD HANURA BINA PUTRA - Rusmi, Salsabila Rafidah Ulfah; Suprijono, Agus; Jacky, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Research and Development (R&D) study aims to: (1) produce a viable, practical, and effective digital comic media using Canva Pro for enhancing intercultural communication skills among fourth-grade students at Hanura Bina Putra Elementary School. (2) The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed. (3) Data collection instruments include validation questionnaires for media experts, subject matter experts, and students, as well as performance assessments. (4) The learning media was deemed suitable, practical, and effective based on product testing: a. Media experts: 98% validity, b. Subject matter experts: 98% validity, c. Students: 92.1% practicality, d. Learning outcomes: 89.5% effectiveness (19 students). This study concludes that the digital comic media for Social Science learning on Indonesian cultural diversity is suitable, practical, and effective for teaching fourth-grade students at Hanura Bina Putra Elementary School.